Message from the President of the United States [electronic resource] : transmitting a convention signed at Washington, February 29, 1892, between the governments of the United States and Her Britannic Majesty, submitting to arbitration the questions which have arisen between those governments concerning the jurisdictional rights of the United States in the waters of Bering, Sea, etc. - United States.; United States. President (1889-1893 : Harrison).; Great Britain 1892 Feb. 29. Treaties, etc. United States ([Washington : s.n., 1892)
With Message from the President of the United States, transmitting further correspondence with Great Britain respecting the fur-seal fisheries in the Bering Sea. Caption title. At head of title: 53d Congress, 1st session, Senate. Ex. Doc. No. 55. Includes bibliographical references. Electronic reproduction. Mode of access: Internet. 44